CIGARETTES, DRUGS, AND BULLYING AMONG ISLAMIC SCHOOL STUDENTS - ELEONORA AGUSTINE; FILDZA NURFAJRINA SUGANDA; HAFIZH AIM ZUFAR; FIRDA HANAN BAHJAH; ANGELINA DAKOSTA; MUHAMMAD ADHITYA NUGRAHA; ERIN WULAN MAGDALENA; CHELSEA SUCIATI NOVIANDRI KUSNAEDI; RAYHAN SALPA YUSUF; RIFKI NUR PRIYANSYAH; HILMY REY HANZYAD SRIGUTOMO; RIZKY RIYADI RAMADHAN; RIZAL NUR FEBRIAN; BUNAIYA RIZKY BALEY; NANDIRA PUTRI KAERUDIN; FINA FERINA INTANIA; MICHELLE LAURA FERDIANA; MAHYANA MAIRUBI KENCANA; FATHIRIZQI FAWWAZ HYANI (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
Juvenile delinquency (such as smoking, drug use, and acts of bullying) is prone to occur after the COVID-19 pandemic and during digitalization, including students in Islamic-based schools. This study aims to examine the perceptions and attitudes of Islamic school students towards smoking, drugs, and bullying, the demographic differences, and the relationship between these variables. The survey was conducted by distributing 26 questions to 94 Islamic school students. Data were processed using descriptive analysis, comparative (t test and ANOVA) and correlation (pearson correlation test). The results showed that almost half of the students had smoked with the male predominance. Perception toward smoking, attitude towards drugs, and bullying were good in each group; shows the contribution of Islamic education to juvenile delinquency. However, perception towards cigarettes and drugs were significantly higher in the upper grade and anti-bullying attitudes were also significantly higher in the group of students who had never smoked. Based on the results of this study, perception towards smoking, attitude towards drugs, and bullying are interrelated so that handling one variable of juvenile delinquency can have an impact on other variables.